Analysis of Memory Usage for Graphic Design Applications on Windows and Linux Operating Systems - Muhammad Khaerudin; Asep Ramdhani M; Wowon Priatna; Joni Warta; Ritzkal Ritzkal (Institute of Computer Science (IOCS), 2022)
The operating system is the most important software on a computer, currently there are several operating systems that are very commonly used in the world of work including Windows, Linux. With these various options, users need to know the characteristics of the OS in running graphic design applications with efficient memory consumption. One of the papers that will be used as a reference in analyzing the OS is a paper with experimental quantitative methods. Referring to the paper, this research will use a quantitative approach with experimental methods, the testing phase is by running a graphic design application on the same hardware but different operating systems, from the experiment a value will be obtained in the form of memory usage numbers when running the application then calculations are carried out using a table. comparison to see which one is more efficient in memory usage, from these results it will be concluded that the characteristics of each OS have their respective advantages and disadvantages.